The Development of Palliative Nursing Competency Assessment Scale of Professional Nurses, Tertiary Hospital - Yimyou, Rosarin; Wisestrith, Wasinee (Journal of The Royal Thai Army Nurses, 2021)
The aim of this study is to develop the competency care assessment of professional nurses. Tertiary Hospital has 387 experienced nurses of 5 years terminally ill patients in inpatient. The study has drawn by multi-stage randomization and divided in to 2 phases. Phase 1 is the Synthesis factors of performance indicator in palliative care and sub-competency programs, build research tools which compose of 9 competency factors, 50 of sub competencies. Passed the content validity examination by experts. The content validity index was 0.86 and the reliability was determined by using the coefficient formula of Cronbach’s alpha which was 0.97. The Data was analyzed by using component factor extraction method. Phase 2 is to construct a palliative care competency evaluation form professional nurses through rubric model. Passed appropriateness of the level of three rubric assessment criteria from experts. The result of this research can be summarized as follows: Palliative care competency factors of professional nurses in Tertiary Hospital have 4 components and can be described by 50 variables with variance of 69.41 percent: 1) Palliative care and pain management described by 59.508% has 13 variables. 2) Knowledge management, ethics and laws spiritual religion and coordination, described by 4.415% and has 13 variables. 3) Communication and care for grief described by 2.928% and has 13 variables. 4) In terms of preparation for the terminal illness and post-mortem care described by 2.565% and has 11 variables. The assessment scale divided the 3 levels of professional nurses.